Teacher education in the PUCPR MATICE project - Ricardo Tescarolo; Patrícia Lupion Torres; Elizete Moreira Matos (Open Praxis, 2008)
This work describes the results of the experience in continuous online training of teachers in the MATICE (Methodologies for Educational and Information and Communication Technology-based Learning) program. This experience was centered on the pedagogical relationship in which the action of the educator becomes decisive. Updating teachers takes on strategic importance for the university in a scenario of constant educational and social changes. The study was carried with 3 classes of teachers from the PUCPR continuous training course in 2006. The procedures adopted for the study were as follows: a review of the literature; building, implementing and following up the project to train teachers in the MATICE program; drawing up and applying the questionnaires; and analysis and discussion of the data obtained. It was decided for this research to carry out a case study. The results of this study show that the continuous teacher training experience was relevant and able to respond to the demands imposed by a new knowledge society; furthermore, it represents a possible way forward for virtual education in PUCPR.